A retrospective study to evaluate the effect of preoperative hormonal therapy on continence recovery - Wang, Yuwen; Zhang, Shun; Huang, Haifeng; Qiu, Xuefeng; Fu, Yao; Lyu, Xiaoyu; Xu, Linfeng; Zhuang, Junlong; Guo, Hongqian (Frontiers in Oncology, 2023)
Objective: To evaluate whether different preoperative hormonal therapy options affect postoperative continence and to identify risk/protective factors for continence recovery. Methods: This is a retrospective analysis of several clinical trials (NCT04356430, NCT04869371, NCT04992026 and NCT05406999). Data from patients treated with hormonal therapy followed by RARP were collected and analyzed. Continence was defined as 0 pad/day or one safety pad. Results: The study included 230 patients with adequate information. The median time to continence recovery is 8 weeks. A total of 216 (93.9%) participants recovered to urinary continence within 12 months after surgery. 21 (9.1%) participants achieved immediate continence. 69, 85, 27 and 14 participants restored continence at 1 month, 1-3 month, 3-6 month, 6-12 month, accounting for 30.0%, 40.0%, 11.7% and 6.1% accordingly. No difference in continence recovery was found among different preoperative hormonal treatment options (p=0.821). Cox regression showed that membranous urethral length (MUL) was the only independent factor influencing urinary continence recovery either in the univariate analysis (OR=1.13, 95%CI: 1.04-1.22, p=0.002) or in the multivariate analysis (OR=1.12, 95%CI: 1.04-1.20, p=0.002). Different preoperative treatment options were not associated with urinary recovery. More advanced preoperative T stage (OR=0.46, 95%CI: 0.24-0.85, p=0.014) delayed the recovery of immediate continence. MUL was associated with continence restoring at 1 month (OR=1.20, 95%CI: 1.03-1.39, p=0.017), 3 month (OR=1.27, 95%CI: 1.07-1.51, p=0.006) , 6 month (OR=1.34, 95%CI: 1.07-1.67, p=0.011) and 12 month (OR=1.36, 95%CI: 1.01-1.84, p=0.044). Conclusion: There is no difference in postoperative continence recovery among ADT, ADT+Docetaxel and ADT+Abiraterone preoperative treatment options. More advanced T stage indicated poor immediate continence recovery. Longer membranous urethral length was a promotional factor for both short-time and long-time continence recovery.